In vitro activities of antifungal drugs against environmental Exophiala isolates and review of the literature. Issue 8 (13th June 2018) - Gülmez, Dolunay; Doğan, Özlem; Boral, Barış; Döğen, Aylin; İlkit, Macit and de Hoog, G. Sybren and Arikan‐Akdagli, Sevtap
Summary: Exophiala is a genus of black fungi isolated worldwide from environmental and clinical specimens. Data on antifungal susceptibility of Exophiala isolates are limited and the methodology on susceptibility testing is not yet standardised. In this study, we investigated in vitro antifungal susceptibilities of environmental Exophiala isolates. A total of 87 Exophiala isolated from dishwashers or railway ties were included. A CLSI M38‐A2 microdilution method with modifications was used to determine antifungal susceptibility for fluconazole, voriconazole, posaconazole, itraconazole, amphotericin B and terbinafine. Minimum inhibitory concentration (MIC) values were determined visually at 48 hours, 72 hours and 96 hours. MIC‐0 endpoint (complete inhibition of growth) was used for amphotericin B and azoles, except fluconazole, for which MIC‐2 endpoint ( 50% inhibition compared to growth control) was used. Both MIC‐0 and MIC‐1 ( 80% inhibition compared to growth control) results were analysed for terbinafine to enable comparison with previous studies. Fungal growth was sufficient for determination of MICs at 48 hours for all isolates except two Exophiala dermatitidis strains. At 72 hours, most active antifungal agents according to GM MIC were voriconazole and terbinafine, followed by posaconazole, itraconazole and amphotericin B in rank order of decreasing activity. While amphotericin B displayed adequate in vitro activity despite relatively high MICs, fluconazole showed no meaningful antifungal activity against Exophiala .